The Political Group of the Magazines Militancia Peronista para la Liberación and De Frente con las bases Peronistas (1973-1974): An Editorial and Militant Experience (Palimpsesto, 2021)
This article focuses on the experience of the political group that published the magazines Militancia Peronista para la liberación and De Frente con las bases Peronistas, between 1973-1974. Our intention is, on the one hand, to briefly reflect on the theoretical and methodological challenge of working with political-cultural magazines that become objects of study and, on the other, placed in the perspective of the new left, to reconstruct the origins of the political group that is formed around the magazines, to identify ideas-strength that crossed the previous and shared spaces of experience and that allow to account for changes and continuities in the process of transformation of their Peronist identity.
Keywords: Political Group; Political-cultural Magazines; New Left; Political Identity; Origins